Analisis Kelayakan Investasi Alat Bioreaktor Anaerob Sebagai Reaktor Proses Fermentasi Nutrisi Organik - Vandi Virnanda; Nawang Sonia; Hery Murnawan; Setijanen Djoko Harijanto (Fakultas Teknik Universitas Tulang Bawang, 2023)
Farmers in Papungan Village, Blitar Regency, are experiencing problems, namely the lack of subsidized fertilizer from the government to meet the demand for fertilizer for their agricultural land. To meet this shortage, farmers apply organic nutrient fertilizers as a substitute for non-subsidized and chemical fertilizers, but the process of making organic nutrient fertilizers requires a long fermentation process, which is 16-30 days. Therefore it is necessary to have an Anaerobic Bioreactor to help speed up the fermentation. This tool is quite expensive for farmers in Papungan village, so it is necessary to analyze the level of investment feasibility of the Anaerobic Bioreactor tool to find out whether it is worth buying or investing. From the calculation results obtained NPV (Net Present Value) of IDR 9,266,620, IRR (Internal Rate Of Return) of 40.1513% and BCR (Benefit Cost Ratio) of 1.0289 so it can be concluded that the purchase of Anaerobic Bioreactors is feasible. Keywords: Bioreaktor Anaerob, Investment, Organic Nutrient Fertilize.